Excitation-induced coherence in a semiconductor microcavity - HEGARTY, JOHN (American Physical Society, 2002)
We measure the dephasing times of high finesse semiconductor microcavities in the strong coupling regime using degenerate four-wave mixing. We find that under certain excitation conditions (near-normal incidence) the dephasing time of the lower polariton branch increases with the excitation intensity. This excitation induced coherence indicates that the lower polariton is acting as a Bose particle.
PUBLISHED
Keywords: Physics